Bidirectional Regulation of Human Colonic Smooth Muscle Contractility by Tachykinin NK2 Receptors - Akihiro Nakamura; Takahiro Tanaka; Akio Imanishi; Makiko Kawamoto; Masao Toyoda; Gaku Mizojiri; Yasuhiro Tsukimi (Elsevier, 2011)
Abstract.: In this study, we attempted to clarify the mechanism of tachykinin-induced motor response in isolated smooth muscle preparations of the human colon. Fresh specimens of normal colon were obtained from patients suffering from colonic cancer. Using mucosa-free smooth muscle strips, smooth muscle tension with circular direction was monitored isometrically. Substance P (SP), neurokinin A (NKA), and neurokinin B (NKB) produced marked contraction. All of these contractions were inhibited by saredutant, a selective NK2-R antagonist, but not by CP122721, a selective NK1-R antagonist or talnetant, a selective NK3-R antagonist. βAla8-NKA(4-10) induced concentration-dependent contraction similar to NKA, but Sar9-Met11-SP and Met-Phe7-NKB did not cause marked contraction. Colonic contraction induced by βAla8-NKA(4-10) was completely blocked by saredutant, but not by atropine. Tetrodotoxin or NG-nitro-l-arginine methyl ester pretreatment significantly enhanced βAla8-NKA(4-10)-induced contraction. Immunohistochemical analysis showed that the NK2-R was expressed on the smooth muscle layers and myenteric plexus where it was also co-expressed with neuronal nitric oxide synthase in the myenteric plexus. These results suggest that the NK2-R is a major contributor to tachykinin-induced smooth muscle contraction in human colon and that the NK2-R-mediated response consists of an excitatory component via direct action on the smooth muscle and an inhibitory component possibly via nitric oxide neurons. Keywords:: NK1 receptor, NK2 receptor, NK3 receptor, human colon, smooth muscle